Study of the Effect of the Segmentation Method on the Power Generation Performance of Rectangular Piezoelectric Energy Harvester. (21st July 2022) - Tian, Xiaochao; Liu, Jinlong; Lin, Jiayin; Li, Shenfang; Wang, Zhicong; Hou, Jun; Zhang, Sida; Yang, Zhigang; Zhu, Jinzhi
Abstract : Since the piezoelectric energy harvester will generate strain zero point when it is bent, it will affect the power generation effect. In this paper, the strain zero point of the cantilever beam of the rectangular piezoelectric energy harvester is studied through theoretical analysis. The main analysis is the specific location of the strain zero point in the first-, second-, and third-order modes of the cantilever beam of the energy capturer. The results of the theoretical analysis are verified by experimenting with different segmentation methods of piezoelectric energy harvesters. The experimental results show that the piezoelectric energy harvester is segmented at 0.275 in the length direction of the piezoelectric ceramic in the second-order mode, and the output power is 5 times that of the nonsegmented state. In the third-order mode, the piezoelectric energy harvester is segmented at 0.16 and 0.61 in the length direction of the piezoelectric ceramic, and the output power is 5.83 times that of the nonsegmented state. The research in this paper provides new ideas and methods for improving the power generation capacity of piezoelectric energy harvesters.